INTERRELIGIOUS RELATION AND VIOLENCE ON RELIGION IN INDONESIA RELIGION PHILOSOPHY PERSPECTIVE - HPW, Nazar Husain (Institut Agama Islam Negeri (IAIN) Sultan Amai Gorontalo, 2014)
This writing gives description about relation among religion followers in Indonesia. The condition of tolerance and the harmony of religion followers in Indonesia is on critical condition. The effort to support multicultural understanding have been done by many sides. The conflict in Indonesia is social religion phenomenon, in whole the violence is happened either on individual level, collective, institution, or the system itself. The mapping model of religious in Indonesia become one alternative for early anticipation. The effort of transformation multicultural understanding is taken by all educators. They are graduated from university should have an ability to transfer the scientific, especially religion tolerance. —–Tulisan ini memberikan gambaran tentang relasi antara pemeluk agama di Indonesia. Kondisi toleransi dan kerukunan umat beragama di Indonesia mengalami situasi kritis. Upaya mendorong pemahaman multikultural telah dilaksanakan banyak pihak. Konflik di Indonesia merupakan fenomena sososial keagamaan, secara keseluruhan kekerasan terjadi pada level individual, kolektif, institusi, maupun sistem. Pemetaan model keberagamaan di Indonesia menjadi satu alternatif antisipasi sejak dini. Upaya transformasi pemahaman multikultural diemban oleh Para pendidik. Mereka yang lulus dari perguruan tinggi sebaiknya mempunyai kemampuan multidimensi dalam mentransformasi keilmuan khususnya toleransi agama.